Pemanfaatan Kotoran Ternak sebagai Energi Terbarukan Melalui Pembangunan Biodigester Komunal - Meidiana, Christia; Perdanasari, Zhuniart Ayu; Dinanti, Dian (Jurnal Rekayasa Mesin, 2020)
The potentials of energy from manure waste was calculated in this study aiming to develop biogas utilization in a rural area. The calculation was conducted based on the result from clustering the non-biogas farmer households which cannot afford individual anaerobic digester (AD). Spatial cluster analysis (SCA) and superimposed technique were used to determine the size of the groups and the location of ADs respectively. Value from SCA showed that the village’s settlement pattern is clustered feasible to apply communal AD for rural biogas development. Meanwhile, a superimposed technique using 3 parameters which are land availability, cow ownership, and topography, generates 43 clusters of farmer households that can supply biogas for cooking. The energy production is estimated at 8.96-39.68 m3/day/household, while the energy demand is approximately 0.65-3.48 m3/day/household. The calculation shows that there is remaining biogas that can be distributed to non-biogas farmer households. Using SCA, 75 non-biogas farmer households were identified to be potentially supplied by biogas. The total energy demand for both biogas and non-biogas farmers households is 2,147.34 MJ/day, while the total potential energy generation from all ADs is 24,560.64 MJ/day indicating a low biogas utilization rate which is only 8.7%. The percentage shows that biogas utilization for an energy source in Dusun Dresel can be more developed by enhancing the distribution network or by converting it into electricity to support rural energy security.